The problem of "significant risk": exploring the public health impact of criminalizing HIV non-disclosure. - Mykhalovskiy, Eric (Social science & medicine (1982), 2011)
Using criminal law powers to respond to people living with HIV (PHAs) who expose sexual partners to HIV or transmit the virus to them is a prominent global HIV public policy issue. While there are widespread concerns about the public health impact of HIV-related criminalization, the social science literature on the topic is limited. This article responds to that gap in knowledge by reporting on the results of qualitative research conducted with service providers and PHAs in Canada. The article draws on a studies in the social organization of knowledge perspective and insights from critical criminology and work on the "medico-legal borderland." It investigates the role played by the legal concept of "significant risk" in coordinating criminal law governance and its interface with public health and HIV prevention. In doing so, the article emphasizes that exploring the public health impact of criminalization must move past the criminal law--PHA dyad to address broader social and institutional processes relevant to HIV prevention. Drawing on individual and focus group interviews, this article explores how criminal law governance shapes the activities of providers engaged in HIV prevention counseling, conceptualized as a complex of activities linking clinicians, public health officials, front-line counselors, PHAs, and others. It emphasizes three key findings: (1) the concept of significant risk poses serious problems to risk communication in HIV counseling and contributes to contradictory advice about disclosure obligations; (2) criminalization discourages PHAs' openness about HIV non-disclosure in counseling relationships; and (3) the recontextualization of public health interpretations of significant risk in criminal proceedings can intensify criminalization.
Keywords: Criminal Law; Female; Focus Groups; HIV Infections; HIV Seropositivity; Humans; Male; Ontario; Public Health; Risk-Taking; Truth Disclosure